Design and Implementation of a Custom Nozzle for Efficient Irrigation System in the Agricultural Faculty of UISU: a Community Service Approach - Jupriah Sarifah; Darlina Tanjung; Marwan Lubis; Ronal H.T. Simbolon; Hafizh Efendi (Sean Institute, 2025)
The Islamic University of North Sumatra (UISU) aims to become increasingly recognized as a top-quality higher education institution, even internationally. This is evident in the ongoing collaborations between the UISU Faculty of Engineering and several educational institutions abroad, particularly in Southeast Asian countries like Thailand and Malaysia. The Faculty of Engineering is currently collaborating with the Saengtham Wittaya School Foundation in Trang, Thailand, for a Sociopreneurship-Based Business Development program for SMSEs in Trang, Thailand. This partnership is a positive step for UISU, as it embodies its vision and mission to expand its reach and become better known internationally. This collaboration is part of the International Mobility of Academics (IMA) program implemented by the ADA Research Center, and is being followed up by the Foundation Saengtham Wittaya School to establish a partnership. This collaboration is expected to benefit all parties, as it discusses many positive aspects for the advancement of education both at home and abroad. The quality and capacity possessed by UISU is believed to be one of the reasons why foreign educational institutions are willing to collaborate with UISU for educational development. The Saengtham Wittaya School Foundation in Thailand chose UISU because it is an Islamic educational institution with a track record of producing high-quality graduates with noble morals, established in 1951. Furthermore, it aims to develop UISU as a higher education institution capable of producing many high-quality individuals in the world of education. The collaboration between UISU and the Saengtham Wittaya School Trang Thailand Foundation will be carried out in the form of collaborative research, community service, journals and development between researchers, institutions, organizations and agencies, including Harapan University Medan, Cendana Polytechnic, Muhammadiyah University of North Sumatra, and the Terrorism Prevention Coordination Forum (FKPT).